Analyzing the City through Cinema: Squatter Areas of Immigrants in Turkish Cinema - Sarıkaya Levent, Yasemin (ICONARCH International Congress of Architecture and Planning, 2017)
By the beginning of 1950s, a massive inner migration started from Eastern and South-eastern Anatolian settlements to metropolitan centres in Turkey. There were different reasons behind this immigration – pull effect of urban prosperity and push effect of rural poverty. The dream of having a prosperous life in the city was represented by a well-known phrase: İstanbul, the city where the streets are paved with gold! Immigration during 1960s brought social and spatial problems alongside. The main social problem was the adaptation of immigrants to urban life. The spatial problem showed itself as a new form of housing provision: Gecekondu, squatter housing. The increase in urban population was so massive that provision of affordable housing was unable to hold the acceleration of population increase. Thus, immigrants have created their own spatial environment in the periphery of the city by the knowledge and daily routines they derived from their hometowns. Those were the prosperity times of Turkish Cinema from 1950s to 1980s. Consequences of rapid industrialization and massive immigration from rural to urban during 1950s and 1960s became basic themes in Turkish Cinema. Films were intended to represent the contradiction of traditional and modern values by also stating the spatial differences between squatter areas and apartment blocks. This representation is carried not only through daily lives of characters, but also spatial environment they are living in. Squatter areas became display for most of the films during 1960s and 1970s. The main concern of the study is to understand the urban environment of 1960s and 1970s under the influence of massive immigration, and social and cultural confusion through cinema. The study will base its discussion on analyzing specific films in order to understand how urban environment created by the immigrants and also from eyes of immigrants is reflected on films.